Management and organizational studies on blue & grey collar workers : diversity of collars - Paliszkiewicz, Joanna; Varoğlu, Demet (International perspectives on equality, diversity and inclusion, 2023)
The digital transformation of work during the COVID-19 pandemic seemed in many ways a fair treaty between employers and employees. However, realistically, its advantages have primarily benefitted white-collar workers with the ability to work from home, excluding a significant proportion of the global workforce, those responsible for providing fresh water, environmental hygiene, transportation, electricity, healthcare and food and security services, who do not have the option of conducting their jobs remotely. The pandemic has thus deepened the gap between white and blue and grey collar workers. Combining both theoretical and empirical studies, Management and Organizational Studies on Blue and Grey Collar Workers focuses on recent issues such as digitalization and migration and their implications for organizational commitment, HRM functions and strategic management processes. Acting as an examination of the changing nature of power between blue and grey collar workers and institutional hierarchies in the light of the COVID-19 pandemic, contributors foreground the importance of these roles as a cornerstone for the competitive power of industries and nations, as well as basic global infrastructure, both now and in future. Highlighting the workers who provide the essential services, maintenance and manufactured goods that power the global economy, Management and Organizational Studies on Blue and Grey Collar Workers supplies essential knowledge on an often overlooked workforce for a variety of disciplines, including human resource management, industrial relations, social psychology, labor economics, gender studies, political science, union studies and health care management.